Pengaruh Kepemilikan Manajerial Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dengan Kebijakan Hutang Sebagai Variabel Intervening - Novia Dian Indri Agustini; enggar nursasi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Background - Increasing company value one of the determining factors is ownership structure. Managerial ownership will tend to improve management performance for the benefit of themselves and shareholders. Institutional ownership can control manager behavior and enhance optimal supervision of managers. The high ownership structure within a company will make managers feel monitored and act more cautiously in the use of debt. Thus, companies must be able to create debt at a certain level so that the company's goals to increase company value can be achieved. Objectives - This study aims to examine the effect of managerial ownership and institutional ownership on firm value with debt policy as an intervening variable. Design / methodology / approach - The type of research used is comparative causal used to explain causal relationships between variables. The population in this study are companies that fall into the Jakarta Islamic Index (JII) index listed on the Indonesia Stock Exchange (BEI) in 2016 - 2018. Samples of 11 companies were selected using the purposive sampling method. This research uses path analysis. The value of the company is measured by Tobin's Q. Managerial and Institutional Ownership is measured by the percentage of share ownership. Debt policy is measured by Debt to Equity Ratio (DER). Findings - Based on the results of the analysis show that (1) managerial ownership affects the value of the company, (2) institutional ownership affects the value of the company, (3) debt policy affects the value of the company, (4) institutional ownership affects the debt policy, (5) Managerial ownership affects the debt policy, (6) Managerial ownership affects the value of the company through debt policy as an intervening variable, (7) institutional ownership affects the value of the company through the debt policy as an intervening variable. Research Implications - This research has implications that can provide an overview and reference for companies related to matters that can affect the value of the company, and can be used as an evaluation material for companies related to company performance during the observation year. Research limitations - The research sample consisted of only 11 companies listed in the Jakarta Islamic Index (JII), with an observation span of only 3 years, and the data used were not yet normal, there was heteroscedasticity and autocorrelation. So the square root transformation is done to improve the data.